2018
DOI: 10.1038/s41556-018-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 links metabolic regulation of ferroptosis to tumour suppression

Abstract: The roles and regulatory mechanisms of ferroptosis (a non-apoptotic form of cell death) in cancer remain unclear. The tumour suppressor BRCA1-associated protein 1 (BAP1) encodes a nuclear deubiquitinating enzyme to reduce histone 2A ubiquitination (H2Aub) on chromatin. Here, integrated transcriptomic, epigenomic and cancer genomic analyses link BAP1 to metabolism-related biological processes, and identify cystine transporter SLC7A11 as a key BAP1 target gene in human cancers. Functional studies reveal that BAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
595
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 705 publications
(621 citation statements)
references
References 71 publications
23
595
0
3
Order By: Relevance
“…Upregulation of GLS2 promotes p53‐dependent ferroptosis . Moreover, tumor suppressors, p53 and BRCA1‐associated protein 1 (BAP1) have been reported to downregulate the SLC7A11 gene, thus inhibiting cysteine uptake and positively regulating ferroptosis in cancer cell lines . Even the acetylation‐defective mutant p53 (K117R, K161R, and K162R) that fails to induce cell cycle arrest, senescence or apoptosis, maintains the ability to reduce SLC7A11 and trigger ferroptosis .…”
Section: Basis Of Ferroptosismentioning
confidence: 99%
“…Upregulation of GLS2 promotes p53‐dependent ferroptosis . Moreover, tumor suppressors, p53 and BRCA1‐associated protein 1 (BAP1) have been reported to downregulate the SLC7A11 gene, thus inhibiting cysteine uptake and positively regulating ferroptosis in cancer cell lines . Even the acetylation‐defective mutant p53 (K117R, K161R, and K162R) that fails to induce cell cycle arrest, senescence or apoptosis, maintains the ability to reduce SLC7A11 and trigger ferroptosis .…”
Section: Basis Of Ferroptosismentioning
confidence: 99%
“…GSH levels were detected using a GSH-Glo Glutathione Assay Kit (Promega, #V6911) following the manufacturer's instructions and a previous report [66].…”
Section: Measurement Of the Intracellular Gsh Levelsmentioning
confidence: 99%
“…Cell death analysis with PI staining was performed according to a previous report [66]. Briefly, cells were seeded into a 6-well plate for different treatment.…”
Section: Measurement Of Cell Death With Propidium Iodide (Pi) Staininmentioning
confidence: 99%
“…No cell lines used in this study are found in the ICLAC database of commonly misidentified cell lines, based on short tandem repeat profiling performed by the vendor. Cell lines with stable expression of Flag-BAP1 WT or mutant were generated as described in our previous publication [18]. Briefly, lentiviral transfections were performed using Lipofectamine 3000 (Life Technologies).…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…Seeking to understand BAP1-mediated tumor suppression, we recently identified SLC7A11 as a key BAP1 target to mediate BAP1's function in tumor suppression through genome wide analyses [18]. We showed that BAP1 reduces H2Aub occupancy on the SLC7A11 promoter and gene body, represses SLC7A11 expression and SLC7A11mediated cystine import, and sensitizes cancer cells to erastin-or cystine depletion-induced ferroptosis.…”
mentioning
confidence: 99%